Determining the motivational factors of the entrepeneurs in Boyacá - Blanco Mesa, Fabio; León Castro, Ernesto; Castro, Mayra; Bermudez, Dario (2021)
The main aim of this article is to performs an analysis on the factors that have motivated entrepreneurs in Boyaca, Colombia to develop their business ideas. The study is carried out with the entrepreneurs enrolled in the Region-Boyacá Brand program, who answered a questionnaire based on 4 motivational dimensions. For the treatment of the collected data we used the method of the experts and the theory of forgotten effects. Findings are shown that for most entrepreneurs the main motivation to develop their business idea is to achieve economic independence. Finally, it is found that the country's economic situation is against the development of entrepreneurship.